Internal curing effect of saturated coral coarse aggregate in high-strength seawater sea sand concrete. (9th May 2022) - Zhou, Linlin; Guo, Shuaicheng; Ma, Wenbo; Xu, Fu; Shi, Caijun; Yi, Yong; Zhu, Deju
Highlights: The correlation between the pore structure of CCA and its internal curing behavior was investigated. Incorporation of saturated CCA can reduce autogenous shrinkage of HS-SWSSC. 10–20% content of saturated CCA is recommended for HS-SWSSC. Abstract: This study characterizes the essential engineering properties of the coral coarse aggregate (CCA) and evaluated its potential utilization as an internal curing agent for high-strength seawater sea sand concrete (HS-SWSSC). The X-ray computed tomography (X-CT) scanning results indicate the internal structure of the CCA is mainly composed of open pores, and the pore diameter is in the range of 46 ∼ 382.1 µm. The water absorption of CCA reaches 15.7% at 24 h, and 90% of the absorbed water can be released at 97.5% relative humidity, which meets the requirements of ASTM C1761 for internal curing. Additionally, the workability and compressive strength of HS-SWSSC first increases and then decreases with the increasing CCA content. In contrast, the setting time of HS-SWSSC generally increases with CCA content. The incorporation of CCA can significantly enhance the internal relative humidity (IRH) of HS-SWSSC and prolong the saturation stage. Then the autogenous shrinkage of HS-SWSSC can be substantially reduced and completely eliminated when the CCA content reaches 20 vol%. The saturated CCA can also improve the hydration degree of HS-SWSCC and densify the interfacial transition zone (ITZ) between the CCA and the cement matrix. Based on the analysis above, the recommended CCA content used in HS-SWSSC is in the range of 10 ∼ 20 vol%. The findings from this study can serve as a valuable reference for utilizing CCA as an internal curing agent in HS-SWSSC.